Traditional Chinese Medicine Intervenes in Vascular Dementia: Traditional Medicine Brings New Expectations - Bai, Xue; Zhang, Meng (Frontiers in Pharmacology, 2021)
Vascular dementia (VD) is one of the most common forms of dementia, referring to a group of symptoms that mainly manifest as advanced neurocognitive dysfunction induced by cerebrovascular disease (CVD). A significant number of studies have shown that traditional Chinese medicine (TCM) has a clinical impact on VD and thus has promising prospects. There have been many discussions regarding the pharmacological mechanisms involved in treatment of the kidney, elimination of turbidity, and promotion of blood circulation. TCM has a prominent effect on improving patients’ cognitive function and quality of life. In this review, we summarize the pathogenesis of VD in modern medicine and TCM, traditional prescriptions, single-agent effective ingredients and their pharmacological mechanisms for treating VD, highlight TCM’s characteristics, and discuss TCM’s multi-targeted mechanism for the treatment of VD.